Mountainous millipedes in Vietnam. III. Two new dragon millipedes from limestone mountains in northern Vietnam (Polydesmida, Paradoxosomatidae, Hylomus), with an identification key to Vietnamese Hylomus species - Anh D. Nguyen; Tam T. T. Vu; Thu-Anh T. Nguyen (ZooKeys)
Two new species of the dragon millipede genus Hylomus Cook & Loomis, 1924 are described from mountainous areas in northern Vietnam, namely Hylomus piccolo sp. nov. and Hylomus borealis sp. nov. The COI barcodes are provided for these species, and an identification key is presented to all Vietnamese Hylomus species.